The Ciberia Project: an experiment in digital hermeneutics - María Goicoechea de Jorge (Texto Digital)
This article presents “Ciberia”, a collection of electronic literature works in Spanish, housed in OdA 2.0., a learning objects’ repository of the University Complutense of Madrid. The Ciberia project involves experimentation at the humanistic and technological level, since it deals with the challenge of archiving digitally-born literary works as well as with the archiving process itself, which we are carrying out in OdA 2.0, a data management system for the creation of learning objects repositories on the Web. OdA allows different researchers to work collaboratively in a simultaneous manner on the data base, they can not only introduce new objects but they can also modify the data model. This entourage allows us to create taxonomies in an inductive rather than deductive manner. The article covers aspects such as the objectives of the collection, the elaboration of Ciberia’s bibliographic card, the process of metadata cleaning and reconciliation with other collections of the Linked Data cloud, such as the CELL Project, and Ciberia’s research and pedagogical functions. Moreover, we will showcase some of its most representative literary works as we revise the process of the collection’s creation.